Resgate histórico das escolas rurais em São João da Boa Vista - SP - Gimenes, Carolina Moraes (Universidade Federal de São Carlos, 2014)
This paper aims to present and analyze fragments of the history of rural education in São João da Boa Vista, in the state of São Paulo. Referring to the principle of totality, the work brings some notes on education in the country and in the state of São Paulo, then to analyze rural education in São João da Boa Vista. For this, at first, part of the literature survey, analysis of laws, annuals teaching the state of São Paulo, and other official documents to official school records and still unofficial including questionnaires, which allowed the observation of the current reality of schools located in the countryside of São João da Boa Vista and knowledge of the profile of the students and their families. It is guided by observation and analysis of these data that the study points to a significant drop in the number of rural schools in the county, showing how the policy of closing these schools stem from numerous factors beyond the individual will remain in the field or not . Finally, it presents some of the possible causes and factors responsible for drawing the current scenario of rural education sanjoanense.
Keywords: Educação rural; Educação no campo; São João da Boa Vista; Education; Rural Education; Education in the field; São João da Boa Vista; CIENCIAS HUMANAS::EDUCACAO